Study of Fermented Food Intervention on the Serum Lipid Profile of Hypercholesterolemia Animals Trial (Meta-analysis) - Tryas, Anisha Ayuning; Astawan, Made; Saraswati, Saraswati (Department of Technology of Agricultural product (THP) Jambi University, 2025)
Abstract— Individuals with hypercholesterolemia (HC) require specific therapy, such as statin medication, to maintain their blood lipid profile (total cholesterol, triglycerides, HDL-C, LDL-C) within the normal range. In vivo, studies have shown that consuming fermented foods for a particular duration can help improve the blood lipid profile of HC animal models. However, meta-analysis studies have not investigated which type of fermented food has the most significant effect on improving the blood lipid profile. The studies included were in vivo research that examined the effects of fermented food interventions on improving the blood lipid profile in HC animal models. The results of this study indicate that fermented food interventions (both plant-based and animal-based) have a highly significant effect (p-value <0.001) on improving the blood lipid profile compared to the HC animal model group without intervention. However, the plant-based fermented food source group tends to show a more significant effect on lipid profiles than those sourced from animals.